Development of Fine Motor Skills and Language in Infants Aged 6-12 Months at Puskesmas Karuwisi, Makassar City - Sriyanah, Nour; Pawenrusi, Esse Puji; Efendi, Suradi; Pratiwi, Dewi Sari; Yati, Mimi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Infants are the age of newborns up to one year, who go through a process of development and growth. This process passes quickly, briefly, and cannot be repeated, so it is called the "golden period". In 2015, 16% of Indonesian children had problems with fine motor development. The study's purpose was to describe the development of fine motor and language in infants aged 6-12 months. This study was quantitative, with a descriptive approach. The population was 103 infants. The population was all mothers with infants aged 6-12 months who visited PUSKESMAS Karuwisi, Makassar City. The sample of this study was infants aged 6-12 months. The sampling technique used was purposive sampling. The sample number was 51 people. The tool used was the Denver Developmental Screening Test (DDST) Observation Sheet. The Findings showed that the most fine motor skills developments was normal category, as many as 42 (82.4%), and language development was normal category, as many as 39 (76.5%). We can conclude that the highest fine motor development of infants aged 6-12 months was normal category, and the highest language development of infants was normal category. It is hoped that every parent should provide the appropriate stimulation according to the infant's developmental stage.